2003
DOI: 10.1080/0267829031000120991
|View full text |Cite
|
Sign up to set email alerts
|

Morphological studies of a hydrogen-bonded LC polymer obtained by photopolymerization in LC solvents

Abstract: Anisotropic morphologies and the phase behaviour of a hydrogen-bonded LC polymer obtained by photopolymerization in two kinds of LC solvent are discussed. The hydrogenbonded LC monomer, 4-(6-acryloyloxyhexyloxy) benzoic acid (A6OBA), was photopolymerized in 4-cyano-4'-hexyloxybiphenyl (6OCB) and in 4-cyano-4'-undecyloxybiphenyl (11OCB), which show a nematic phase and a smectic A phase, respectively. After photopolymerization, the LC media were removed by extraction and the pure polymer was observed by scanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Such a CLC reaction field has successfully been employed for the polymerization of polymerstabilized CLC materials. [11,12] The surface structures of polymers synthesized using CLC or smectic A (SmA) matrices have been observed after removal of the LC, [13][14][15] and it has been confirmed that the polymerization of helical polyacetylene in CLC, [16] and polyaniline [17,18] and poly(3,4-ethylenedioxythiophene) (PEDOT) in micellar lyotropic LC by an electrochemical method results in molecular imprinting. Optically active PEDOT has been synthesized using a LC solution of deoxyribonucleic acid (DNA), [19] and nanohybrids of PEDOT/ schizophyllan have been produced by template polymerization.…”
Section: Introductionmentioning
confidence: 87%
“…Such a CLC reaction field has successfully been employed for the polymerization of polymerstabilized CLC materials. [11,12] The surface structures of polymers synthesized using CLC or smectic A (SmA) matrices have been observed after removal of the LC, [13][14][15] and it has been confirmed that the polymerization of helical polyacetylene in CLC, [16] and polyaniline [17,18] and poly(3,4-ethylenedioxythiophene) (PEDOT) in micellar lyotropic LC by an electrochemical method results in molecular imprinting. Optically active PEDOT has been synthesized using a LC solution of deoxyribonucleic acid (DNA), [19] and nanohybrids of PEDOT/ schizophyllan have been produced by template polymerization.…”
Section: Introductionmentioning
confidence: 87%
“…The monomer, 4-(6-acryloyloxyhexyloxy)benzoic acid (1), was synthesized according to the method outlined by Broer et al [10] The thermal properties of 1 have been described in a previous paper. [8] The chiral dopant, (S)-(þ)-4-cyano-4 0 -(2-methylbutoxy)biphenyl (3), was prepared by etherification of 4-cyano-4 0 -hydroxybiphenyl and (S)-(þ)-1-bromo-2-methylbutane in the presence of K 2 CO 3 in a DMF solution. The molecular structure of 3 was confirmed by means of NMR spectroscopy and mass spectrometry.…”
Section: Experimental Partmentioning
confidence: 99%
“…[8] After UV irradiation, the samples were extracted with ethanol to remove the cyanobiphenyl derivatives and unreacted monomers. The resulting polymers remaining on the glass plates were observed with an SEM.…”
Section: Blend Preparation and Photopolymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface structures of polymers synthesised in LC matrices using light-induced polymerisation methods have been studied. [12][13][14][15][16] A LC solvent was employed for the preparation of polyacetylenes using the Ziegler-Natta catalytic system over 20 years ago. [17][18][19] Syntheses of polyacetylene in NLC under an applied magnetic field [20] and using a gravity flow technique [21] were performed to obtain films with conductivity anisotropy.…”
Section: Introductionmentioning
confidence: 99%